Prevention of acute radiation-associated toxicity by traditional Chinese medicine Tianwang buxin mini-pills in patients with head and neck cancer - Kao-Shin Lin; Yee-Min Jen; Tsu-Yi Chao; Yaoh-Shiang Lin; Li-Hsiang Wang; Chien-Jung Lin; Yi-Chang Su; Shung-Tai Ho (Journal of Medical Sciences, 2014)
Background: Anemia and oral mucositis are main side effects of radiotherapy (RT) and are important factors affecting the quality of life (QOL) in head and neck cancer (HNC) patients treated with RT. This study aimed to explore the safety and therapeutic efficacy of Tianwang Buxin Mini-pills (TWBXM) for the prevention of acute RT toxicity in HNC patients by using a randomized, double-blind and placebo-controlled study design. Patients and Methods: Seventy-three HNC patients participated the study. They were randomized into a treatment group (n = 38) and a control group (n = 35). All patients received daily either TWBXM treatment or placebo starting from the initiation of RT until 1-month follow-up after RT completion. All patients were evaluated for QOL, acute RT toxicities and laboratory data (hemoglobin [Hgb], white blood cell and platelet) at 3 time points: Pre-RT, upon RT completion and at TWBXM completion. Results: The TWBXM group maintained normal levels of Hgb during the duration of the study while the placebo group showed a decrease in Hgb (P = 0.035). Conclusions: This study demonstrated the safety and efficacy of TWBXM applied in the HNC patients receiving RT. It prevented the decrease of Hgb in HNC patients undergoing RT treatment as well 1-month-post-RT treatment. Further studies are needed to assess the effects of TWBXM for the prevention of other RT toxicities.